Aristotelian Background of Gregory Thaumaturgus’s Theory of ‘Mixture’ in the Ad Theopompum de passibili et impassibili in Deo (CPG 1767) - Celia, Francesco (Annali di Scienze Religiose, 2024)
Abstract In a dialogue with a pagan over the Christian view that God is impassible despite suffering from Passion, Gregory claimed that this capacity is analogically manifested in the natural world. The discussion of certain physical phaenomena provides Gregory with the basis for the assertion that God is impassible while it is in ‘contact’/‘participation’/‘mixture’ with ‘things which cause passions’. This paper will argue that the theory of mixture which underlies Gregory’s line of reasoning is not Stoic, as earlier scholars have alleged (L. Abramowski), but presupposes some (likely indirect) acquaintance with Aristotle’s account of mixtures in the De generatione et corruptione. Abstract In un dialogo con un pagano sulla credenza cristiana secondo cui Dio è impassibile nonostante la passione, Gregorio sostiene che questa capacità si manifesta analogicamente nel mondo naturale. La discussione di alcuni fenomeni fisici fornisce a Gregorio la base per l’affermazione che Dio è impassibile mentre è in ‘contatto’/‘partecipazione’/‘mescolanza’ con ‘cose che causano passioni’. Questo articolo sosterrà che la teoria della mescolanza che sta alla base del ragionamento di Gregorio non è stoica, come hanno affermato alcuni studiosi precedenti (L. Abramowski), ma presuppone una qualche conoscenza (verosimilmente indiretta) del resoconto aristotelico sulle mescolanze nel De generatione et corruptione.